Performance analysis of a nanorefrigerant (hydrocarbon+ CuO) based refrigeration system - Kaushik, Rajneesh (My University, 2015)
Refrigeration and air conditioning plays a crucial role in order to fulfill the day today human needs and industrial requirements. The performance of any such system largely depends upon the performance of its integral subsystems like; evaporator, compressor, condenser, expansion valve and the thermal performance of the type of the refrigerant being used. The performance of these conventional refrigeration systems depends on the inherited poor thermal properties of the refrigerant. In the presented work, an attempt has been made to review the performance of such system by replacing the conventional refrigerant (R134a) with nanorefrigerant (hydrocarbon+CuO). The experimental work was done on the standardized experimental set up which was fabricated and made to function in the department lab. It has been found that the refrigerant’s characteristics can be enhanced by mixing nano particles to the base refrigerant. The nano particles improve its heat transfer performance, which is desirable to increase refrigeration effect & coefficient of performance of the system. In the experimental set up, hydrocarbon refrigerant along with CuO nano particles has been used. Hydrocarbon refrigerant is more eco friendly than the conventional refrigerants such as R134a. CuO nano particles are introduced in vapour compression system with the help of charging line & small straw. Different tests are carried out & reading of temperature, pressure, energy consumed was taken at different points & under different conditions. COP, Cooling speed, condenser temperature drop & evaporator temperature gains are calculated. The results showed that there is improvement in COP (4.7-11%) and also in cooling speed (8.4~18.6%) with increase of nanoparticles concentration. This is due to better thermo physical properties of the nano refrigerants. The experiments also showed that nanorefrigerant work normally in vapour compression systems. Thus, CuO nano particles can be used in refrigeration systems for efficient working. Keywords: Copper oxide nanoparticles, nano-refrigerant, thermal conductivity, cooling speed, COP, power consumption
ME-Thermal Engineering-Thesis
Keywords: nanofluid; CuO; nanorefrigerant; hydrocarbon; COP; mechanical engineering; thermal engineering; med